DESIGNING NARRATIVE LEARNING MATERIAL AS A GUIDANCE FOR JUNIOR HIGH SCHOOL STUDENTS IN LEARNING NARRATIVE TEXT - Aprilia Riyana Putri (Universitas Islam Nahdlatul Ulama Jepara, 2016)
There are so many texts are be taught by the English teacher to their students. In junior High School level, starts at the seventh grade until nine grades the students will learn so many various texts; they are descriptive texts, procedure texts, recount text, narrative text and report text. Every text has different functions, generic structures and also grammatical features. It helps the students to differentiate between one text and others. In descriptive text, the students will learn how to describe people, things and place in specific, in procedure text, the students will learn how to make something and how use things, in recount text, the students will learn how to tell about their real experience in the past, in the narrative the students will learn how to tell some stories and in report text, the students will learn how to provide natural phenomena and non natural phenomena. Here, the researcher tries to design a narrative book, it means she just take one text, which is a narrative text. The researcher focus only take a narrative text because it has some kinds of stories, they are; Myth, Fable, Legend, Folktale and Fairy Tale. The book content is not only the narrative text, but complete with vocabulary and the exercises. The researcher also hopes that most of students love reading through many kinds of stories from narrative book from her narrative book design. Hopefully, after this book finished, it can help for students in learning text, especially for narrative text. It also can help the English teacher to explain narrative text briefly and easily.